Kamus Visual Pembelajaran Biologi SMA Berbasis Riset Asosiasi Vegetasai Dasar Lahan Gambut Pasca Kebakaran - Firdaus, L.N.; Nursal, Nursal; Firdaus, Yuslim; Gani, Ridho Abdul (Indonesian Biology Teachers, 2018)
Abstract. Peatland fires in Riau province have a negative impact on the natural ecosystem, especially very influential on plants. However, many plants can grow back after the fire. This study aims to produce a visual dictionary of learning Biology SMA by utilizing the results of studies on ecosystems in post-fire peatlands. For this purpose, a survey study has been conducted in Rimbo Panjang Village, Kampar District, Riau Province from February to October 2017. Quadratic methods and sampling techniques are purposively applied to the gradient of fire incidents in 2009, 2013, 2014, 2015, 2016 and 2017. Parameters observed in the form of species composition, environmental factors and associated vegetation associations of post-fire peatland vegetation. Data were analyzed using 2x2 contingency table descriptively and qualitatively. Based on the results of the study found 32 species and 18 families of basic vegetation on post-fire peatlands. The association of peatland vegetation found in 42 pairs of species, of which 33 pairs of species are positively associated while 9 couples are negatively associated. The results of research can be utilized for the development of learning visual dictionary of High School Biology class X (KD 3.10). Trials using the resulting visual dictionary and its benefits to the enrichment of classical learners learning materials are strongly recommended.Â Keywords: Association, peatland, post fire vegetation base